تطوير مستوى التعقيد المعرفي في الكتابة الأكاديمية : استخدام تصنيف بلوم المعرفي لتطوير طريقة لمراجعة الدراسات السابقة - Mikail Ibrahim; Nurhasma Muhamad Saad; Wahida Mansor; Sulaiman Ismail (Al-Madinah International University, 2024)
his scientific research aims to shed light on the possibility of applying Bloom's cognitive taxonomy in scientific writing at the level of undergraduate and postgraduate studies. In this paper, the researchers focused on how to employ this cognitive classification in developing scientific research writing in general and reviewing previous studies and research literature in particular. This knowledge classification provided mechanisms to assist students in developing knowledge complexity and conducting scientific research of international quality. Bloom's cognitive classification is a cognitive structure through which it tries to assess the students' level of knowledge in terms of what they should acquire from the intellectual and cognitive abilities. Bloom and colleagues categorized this model hierarchically from the lowest to the highest levels of knowledge; They are remembering, comprehending, applying, analyzing, synthesizing and finally evaluating. The researchers discovered the possibility of benefiting from Bloom's cognitive model in raising the students' writing level, especially after applying it in practice, and the students' interest in it and their benefit from it, especially after the feedback process. Therefore, feedback is essential for students to benefit from this model in order to direct them to what should be done to raise their scientific level and develop their writing skills. In order for students to benefit from reviewing previous studies, supervisors should provide comments that show their current level and mechanisms of development to the next level. This research showed the levels of Bloom's Taxonomy, the specifics of each level, and how to take advantage of it to transfer students from the lower level to the higher level. In order for students to benefit from reviewing previous studies, supervisors should provide comments that show their current level and mechanisms of development to the next level. This research showed the levels of Bloom's Taxonomy, the specifics of each level, and how to take advantage of it to transfer students from the lower level to the higher level. In order for students to benefit from reviewing previous studies, supervisors should provide comments that show their current level and mechanisms of development to the next level. This research showed the levels of Bloom's Taxonomy, the specifics of each level, and how to take advantage of it to transfer students from the lower level to the higher level.